Backmatter (Copyright Transfer Agreement Form, Publication Ethics, Submission Information) - Dian Bayu Firmansyah (Jurnal Lingua Idea, 2019)
Jurnal Ilmiah Lingua Idea, Volume 10, Issue 2, December 2019